Functional evaluation indicates physical losses after hematopoietic stem cell transplantation - Souza,Clarissa Vasconcellos de (2012)
OBJECTIVE: To perform a function evaluation of patients before and after hematopoietic stem cell transplantation. METHODS: From November 2008 to November 2010, 29 female (58%) and 21 male patients (42%) with median age of 48 years (range: 24-67) were enrolled in this study. Data collection was performed before and after autologous or allogeneic hematopoietic stem cell transplantation. Evaluation instruments included the 2-minute walking test to evaluate gait performance with assessment of the oxygen saturation, heart rate and Borg Scale before and after the test; grip strength for strength evaluation, Schober Test for spine mobility testing and maximum and adapted activity scores of the Human Activity Profile questionnaire to test functionality in daily activities. RESULTS: Fifty patients were evaluated at baseline; six did not undergo hematopoietic stem cell transplantation (three died, one refused and two were excluded). Thus 44/50 (88% - 21 allogeneic and 23 autologous) transplantations were performed. Only 33 of the 44 patients (75%) performed evaluations after transplantation (nine died and two were excluded). Of the patients who performed both evaluations, significantly lower values were found in the evaluation after transplantation for the 2-minute walking test (p-value = 0.004), grip strength of both right and left hands (p-value = 0.004 and p-value < 0.0001, respectively), the Schober Test, and maximum and adapted activity scores (p-value < 0.0001). The heart rate was higher (p-value = 0.01) before the 2-minute walking test and oxygen saturation was higher (p-value = 0.02) after. CONCLUSION: Statistical differences indicate functional impairment after transplantation showing physical losses in this population.